From love between women to love between dolls: an actress report on her creative processes (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article reports part of two artistic processes in Puppet Theater that its author developed during the Master's degree in Performing Arts in UFU (Universidade Federal de Uberlândia). The creative trigger was the author's need to know more theater of animated forms shows that would present love stories between women (like lesbians and bisexuals), since theauthor herself is homosexual. The processes’ display brings up reflections and creations made inshadow theater, object theater and lambe-lambe theater, besides dialoguing with women artistswho served as inspiration and great influence on the scenic experiences and the spectacle created by the respective author.